2018
DOI: 10.1128/jb.00216-18
|View full text |Cite
|
Sign up to set email alerts
|

The OmpR Regulator of Burkholderia multivorans Controls Mucoid-to-Nonmucoid Transition and Other Cell Envelope Properties Associated with Persistence in the Cystic Fibrosis Lung

Abstract: Bacteria from the complex grow in different natural and man-made environments and are feared opportunistic pathogens that cause chronic respiratory infections in cystic fibrosis patients. Previous studies showed that mucoid clinical isolates grown under stress conditions give rise to nonmucoid variants devoid of the exopolysaccharide cepacian. Here, we determined that a major cause of the nonmucoid morphotype involves nonsynonymous mutations and small indels in the gene encoding a response regulator of a two-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…We showed that the EnvZ R397H substitution alters the balance of porin production with down-regulation of the major outer membrane pore, OmpF and up-regulation of the narrow outer membrane pore, OmpC. EnvZ controls activity of OmpR, which is known to control the balance of porin production as well as biofilm formation under low medium osmolarity conditions (17,40). OmpF is well characterised as an entry point for β-lactams due to the molecules’ physiochemical properties, which makes entry possible through this porin which has a larger pore size than OmpC (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the EnvZ R397H substitution alters the balance of porin production with down-regulation of the major outer membrane pore, OmpF and up-regulation of the narrow outer membrane pore, OmpC. EnvZ controls activity of OmpR, which is known to control the balance of porin production as well as biofilm formation under low medium osmolarity conditions (17,40). OmpF is well characterised as an entry point for β-lactams due to the molecules’ physiochemical properties, which makes entry possible through this porin which has a larger pore size than OmpC (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…reported parallelism in an OmpR-like response regulator, which is involved in the mucoidy phenotype of B . multivorans , and later showed its association with persistence in the CF lungs [54, 60]. We found two related multi-mutated genes encoding an OmpR family-sensor histidine kinase (BMUL_3678) and an OmpR family response regulator (BMUL_0075).…”
Section: Discussionmentioning
confidence: 99%
“…Another important regulator of CEP biosynthesis is the response regulator OmpR. In the Bcc strain B. multivorans, OmpR was shown to be important for the mucoid to non-mucoid switch (Silva et al, 2018). Interestingly, several Bcc non-mucoid isolates produce large amounts of the polysaccharide CEP when tissue of the natural host plant onion was provided as nutrient source (Bartholdson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In silico analysis of P. phymatum gene cluster (Bphy_1056–Bphy_1077) suggested that it is involved in the biosynthesis of CEP, a branched acetylated heptasaccharide also produced by many strains of the Burkholderia sensu latu , which are opportunistic pathogens ( Conway et al, 2004 ; Cescutti et al, 2010 ; Ferreira et al, 2010 ; Hallack et al, 2010 ; Cuzzi et al, 2012 ). The role of CEP and particularly the associated switch to mucoid colonies in Burkholderia virulence is controversially discussed in the literature ( Govan et al, 1993 ; Conway et al, 2004 ; Zlosnik et al, 2008 , 2011 ; Silva et al, 2018 ). Recent data suggest that CEP is important for chronic infections and appears to be rather counter-productive for acute virulent infections ( Silva et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation